KEADAAN COVID-19 SEBAGAI FORCE MAJEURE DALAM PERJANJIAN BAGI PELAKU BISNIS - Juliastrid, Juliastrid; Novela, Devina; Diana, Diana (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Covid-19 is one of the newest types of virus variants that has caused unrest in society. Therefore the government made various policies to tackle the spread of this virus. In addition to having an impact on health, it also has an impact on the community's economy. The existence of restrictions makes the parties who have an agreement unable to fulfill their obligations, this can be said to be a default. However, this can be justified when there are compelling circumstances or Force Majeure. There is a difference between Force Majeure Civil Law and Common Law which lies in agreement and proof, then the provisions in the Civil Code have explained that the Covid-19 situation can be said to be a Force Majeure if it fulfills 4 elements. And government policies when tackling Covid-19 in accordance with the Presidential Decree can be categorized as a Force Majeure with aspects of unexpected events such as natural disasters and others.